Faster return to work after psychiatric consultation for sicklisted employees with common mental disorders compared to care as usual. A randomized clinical trial - Christina M van der Feltz-Cornelis (Dove Medical Press, 2010)
Christina M van der Feltz-Cornelis1, Rob Hoedeman2, Fransina J de Jong3, Jolanda AC Meeuwissen3, Hanneke W Drewes3, Niels C van der Laan4, Herman J Adèr51Department of Developmental, Clinical and Crosscultural Psychology, Tilburg University, Tilburg, The Netherlands; 2Department of Health Sciences, University Medical Center Groningen, The Netherlands; 3Trimbos instituut, NIMHA, Utrecht, The Netherlands; 4Psychiatric Consultation Practice, The Netherlands; 5Retired from Department of Clinical Epidemiology and Biostatistics, VU University Medical Center, Amsterdam, The NetherlandsIntroduction: Return to work (RTW) of employees on sick leave for common mental disorders may require a multidisciplinary approach. This article aims to assess time to RTW after a psychiatric consultation providing treatment advice to the occupational physician (OP) for employees on sick leave for common mental disorders in the occupational health (OH) setting, compared to care as usual (CAU). Methods: Cluster randomized clinical trial evaluating patients of 12 OPs receiving consultation by a psychiatrist, compared to CAU delivered by 12 OPs in the control group. 60 patients suffering from common mental disorders and ≥ six weeks sicklisted were included. Follow up three and six months after inclusion. Primary outcome measure was time to RTW. Intention-to-treat multilevel analysis and a survival analysis were performed to evaluate time to RTW in both groups. Results: In CAU, referral was the main intervention. Both groups improved in terms of symptom severity and quality of life, but time to RTW was significantly shorter in the psychiatric consultation group. At three months follow up, 58% of the psychiatric consultation group had full RTW versus 44% of the control group, a significant finding (P = 0.0093). Survival analysis showed 68 days earlier RTW after intervention in the psychiatric consultation group (P = 0.078) compared to CAU. Conclusion: Psychiatric consultation for employees on sick leave in the OH setting improves time to RTW in patients with common mental disorders as compared to CAU. In further research, focus should be on early intervention in patients with common mental disorders on short sick leave duration. Psychiatric consultation might be particularly promising for improvement of RTW in those patients.Trial registration number: ISRCTN: 86722376Keywords: psychiatric consultation, mental disorders, RCT, sickness absence, major depressive disorder, anxiety disorder, somatoform disorder